2001
DOI: 10.1002/1521-396x(200101)183:1<81::aid-pssa81>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Optical Properties of GaN-Based Nanostructures by Charge Screening

Abstract: In this paper we will show the influence of doping and free charge screening of polarization fields on the optical and electronic properties of GaN-based nanostructures. Modulation-doped nanostructures can be used to enhance the oscillator strength of the fundamental transition energy. The free charge and doping are shown to be an additional degree of freedom for GaN-based device design.1. Introduction Nitride-based nanostructures are nowadays used in both electronic and optoelectronic devices. In the first ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Starting from 2000, GaN has become one of the most important semiconductors after Si [5]. It is no wonder that it finds ample application in LED lighting and displays of all kinds, lasers, detectors, and high-power amplifiers.…”
Section: Conventional Semiconductorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Starting from 2000, GaN has become one of the most important semiconductors after Si [5]. It is no wonder that it finds ample application in LED lighting and displays of all kinds, lasers, detectors, and high-power amplifiers.…”
Section: Conventional Semiconductorsmentioning
confidence: 99%
“…By using equations (2-18b) and (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), an expression for absorption coefficient in terms of the bandgap energy is found by [115] ℎ…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have seen that GaN channel is more useable than silicon channel. The GaN has wide band gap of 3.4 eV affords its special properties for applications in optoelectronic high-power and highfrequency devices [1] [2]. GaN is a very hard (12±2 GPa [3]), mechanically stable wide bandgap semiconductor material with high heat capacity and thermal conductivity [4], but we have found that the GaN is better channel material than Si-FinFET.…”
Section: Introductionmentioning
confidence: 99%